Penyesuaian Sosial Remaja Madya Akibat Perceraian Orang Tua di Banyuwangi - Melani Rahmawati; Riza Noviana Khoirunnisa (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research was conducted to determine the social adjustment of middle-aged teenagers who were victims of divorce in Banyuwangi using the case study method. Semi-structured interviews and observations were data collecting methods carried out with three participants who were the victim of divorce and four significant others. In the discussion, the researcher using thematic analysis technique by dividing several main themes and will divide several main themes 1.) the description of the effects of divorce, 2.) Aspects of social adjustment, and 3.) Social adjustment factors. This study revealed that the three participants whose families had divorced had almost the same social adjustment process, however, differed in dynamics and several aspects. Meanwhile, the influencing factors is environmental factor, especially the community environment to undergo social adjustments in their environment.